Factors affecting help-seeking behaviour of women with urinary incontinence; a commentary providing insights for osteopaths. (September 2016) - Robinson, Maria; Humpage, Claire
Abstract: Urinary incontinence (UI) is a common condition, affecting approximately one third of women over the age of forty. Recommended first-line management in the majority of cases consists of simple, conservative, self-help measures, and the condition is often highly preventable and treatable. Despite this, many affected by symptoms do not seek help from healthcare providers and do not mention their symptoms when attending for appointments. Rather than seeking help, women will often adopt coping strategies, sometimes to the detriment of their health and wellbeing. Osteopaths are likely to encounter a large proportion of women experiencing symptoms of UI, but may be unaware that their patients are affected by the condition. An extensive body of literature examining the factors that may affect the help-seeking behaviour of women experiencing UI exists and an exploration of this was undertaken in order to consider these factors in the context of osteopathic practice. The factors affecting whether an individual would seek help for urinary symptoms can be described in terms of the triggers that prompt an individual to seek help and also in terms of the barriers that might prevent or delay this. An appreciation of these, along with the risk factors and treatment options may be considerations for osteopaths when treating their female patients. The implications for providing advice to patients should be considered in light of this.